The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12144-020-01260-8
|View full text |Cite
|
Sign up to set email alerts
|

Are women the more empathetic gender? The effects of gender role expectations

Abstract: The present research aimed to extend the state of knowledge regarding the relationship between self-perceived empathy and traditional gender roles and placed particular focus on the contextual conditions under which gender differences in empathy are present, can be created, or eliminated. Across two studies, women rated themselves higher in empathy than men in all experimental conditions, whereas an objective female superiority in emotion recognition was only evident in one condition. In Study 1 (n = 736), usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
7
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 26 publications
4
58
7
7
Order By: Relevance
“…Future studies can further investigate it. Even though past studies found that women tend to have higher empathy than men [76,77], the current finding did not show such a trend. This may be due to other factors, such as the context and gender role expectations [76], rather than simply self-reported biological sex in the questionnaire.…”
Section: Potential Sex Differencescontrasting
confidence: 99%
See 1 more Smart Citation
“…Future studies can further investigate it. Even though past studies found that women tend to have higher empathy than men [76,77], the current finding did not show such a trend. This may be due to other factors, such as the context and gender role expectations [76], rather than simply self-reported biological sex in the questionnaire.…”
Section: Potential Sex Differencescontrasting
confidence: 99%
“…Even though past studies found that women tend to have higher empathy than men [76,77], the current finding did not show such a trend. This may be due to other factors, such as the context and gender role expectations [76], rather than simply self-reported biological sex in the questionnaire. A meta-review on empathy and sex differences [78] has also identified a few important factors that future studies can consider for further investigation of sex differences and empathy.…”
Section: Potential Sex Differencescontrasting
confidence: 99%
“…Evolutionary accounts of gender-related differences in empathy (Christov-Moore et al, 2014) posit that empathic concern may be especially advantageous for females to protect and nurture children (Decety & Svetlova, 2012). In contrast, adult studies suggest that gender differences in empathy emerge from socialized beliefs about gender roles, where empathy is viewed as a typically feminine trait (Löffler & Greitemeyer, 2021). Although our data cannot address this debate, we do find gender differences present in aspects of empathy consistent with past research.…”
Section: Discussionsupporting
confidence: 78%
“…Empathizing refers to the ability to recognize another person's mental state ("cognitive empathy") and the tendency to respond to it with an appropriate emotion (Greenberg et al, 2018;Archer, 2019). Men tend to score higher on systemizing (Cohen's ds are generally medium to very large, ranging between 0.31 and 1.21), while women, on average, have higher scores on empathizing (Cohen's ds generally ranging between -0.39 and -0.87) (Greenberg et al, 2018;Archer, 2019; see also Löffler and Greitemeyer, 2021).…”
Section: Personalitymentioning
confidence: 97%